PROCALCITONIN TEST IN RHEUMATIC DISEASES - G. M. Tarasova; B. S. Belov; E. N. Aleksandrova; A. A. Novikov (Научно-практическая ревматология, 2014)
Estimation of serum procalcitonin (PCT) levels is of great interest in rheumatology in both the diagnosis of coinfectionsand the differential diagnosis between rheumatic disease activity and the current infectious process.Objective: to estimate the value of PCT as a specific marker for generalized and local infection in rheumatic patients.Subjects and methods. A retrospective study investigated the case histories of 100 inpatients examined and treated at the V.A. Nasonova Research Institute of Rheumatology. Serum PCT concentrations were determined by a quantitative electrochemiluminescence assay using a Cobas E 411 analyzer (Roche, Switzerland).Results. Infectious diseases were diagnosed in 41 of the 100 patients. The infectious process was generalized and local in 11 and 30 cases, respectively. In the patients with generalized infection, the level of PCT was more than 2.0 ng/ml in 81.8% of the cases. In the local infection and non-infection groups, it was below 0.5 mg/ml in 70 and 84.7% ofcases, respectively. In the generalized infection group, the content of PCT was significantly higher (3.6 [2.3; 10.5]) than in the local infection (0.24 [0.15; 0.7]; р = 0.004) and non-infection (0.15 [0.09; 0.26]; р = 0.0001) groups. It did not depend on rheumatic disease activity. C-reactive protein (CRP) levels and erythrocyte sedimentation rate (ESR)correlated with PCT concentrations in different patient groups. ROC analysis showed the optimal sensitivity (82%) and specificity (98%) of PCT as a marker of systemic infection only in the rheumatic patients with its concentration of ≥2.3 ng/ml.Conclusion. The determination of PCT is certain to contribute to the diagnosis of generalized infections and the differential diagnosis of systemic rheumatic diseases and infectious ones.